Infrared drying kinetics and moisture diffusivity modeling of pork - Jing, Ling; Zhaosheng, Teng; Haijun, Lin; He, Wen (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: This study investigated the drying kinetics of pork slice in infrared drying condition. Drying temperature, slice thickness and initial moisture content were selected as influencing factors on the drying characteristics and drying rate of pork slice. Drying curves obtained from the experimental data were fitted to semi theoretical and/or empirical thin layer drying models. The effects of drying temperature and slice thickness on the model constants were evaluated by the multiple regression method. All the models were compared according to three statistical indexes, i. e., root mean square error, chi-square and modeling efficiency. The slice thickness, drying temperature and initial moisture content have significant influences on the effective diffusivity coefficient of pork. The results showed that the drying rate of pork slices increased with the increases of drying temperature and initial moisture content. The decreases of slice thickness also led to an increase of drying rate. The Henderson and Pabis model can best describe the drying curves of pork. Keywords: infrared drying, pork slice, drying kinetics, effective moisture diffusivity, multiple regression analysis DOI: 10.3965/j.ijabe.20171003.2518 Citation: Ling J, Teng Z S, Lin H J, Wen H. Infrared drying kinetics and moisture diffusivity modeling of pork. Int J Agric & Biol Eng, 2017; 10(3): 302–311.